Aspects that affect the shear bands in numerical simulations of strain plane test using finite elements in a hypoplastic constitutive model - Ramos Cañón, Alfonso Mariano; Lizcano Peláez, Arcesio (Rev. Téc. Fac. Ing. Univ. Zulia)
In conventional geomechanical analysis performed with the Finite Element Method, the orientation of the failure surface or shear band depends on the orientation of the elements. To avoid this undesirable dependence, the analysis in finite elements has been developed based on non conventional continuum media. However, there is not available geomechanical technical literature related with a methodic research upon the factors that influence the shear band formation. This paper presents a systematical study about factors that affect the shear band formation. Simulations of biaxial tests (plain strain) in Karlsruhe sand were undertaken, considering a hypoplastic constitutive model in a Boltzmann continuum. It is concluded that: the shape of the shear band depends on the inclination of the finite elements, the relation stress-strain depends on the mesh, the thickness of the shear band is independent on the number of weak elements but is function of the size of the finite elements and the inclination of the shear band is controlled by the inclination of the elements.